Galectin-3 as a Marker of Cardiorenal Syndrome in Patients with Chronic Heart Failure - V. I. Podzolkov; N. A. Dragomiretskaya; A. V. Kazadaeva; Yu. G. Belyaev; A. V. Tolmacheva (Рациональная фармакотерапия в кардиологии)
Aim. To assess the effect of renal dysfunction on the galectin-3 level in patients with chronic heart failure (HF) with preserved, intermediate and reduced left ventricular ejection fraction (EF).Material and methods. Along with a clinical examination, 69 patients with HF (NYHA class II-IV) underwent tests for the level of NT-proBNP and galectin-3 in serum using enzyme immunoassay.Results. Study participants were divided into 3 groups: 23 patients with preserved EF (HFpEF), 26 patients with midrange EF (HFmrEF), 20 patients with reduced EF (HFrEF). There was a trend to increase the concentration of galectin-3 with increase in NT-proBNP level. Correlation analysis showed significant feedback (r=−0.41, p<0.05) between galectin-3 and EF only in patients with preserved systolic function. In the same group of HFpEF patients, the maximum serum galectin-3 level was 10.5 [6.5; 14.5] ng/ml. Serum galectin-3 level showed negative correlated with the GFR in patients with CHF (r=−0.513, p<0.05). In patients with HF and glomerular filtration rate (GFR) <60 ml/min/1.73 m2 it was higher than in patients with GFR>60 ml/min/1.72 m2 (9 [5.3; 12.6] ng/mL vs 11.8 [6.2; 15.3] ng/mL, p<0.05). According to the ROC-analysis data, galectin-3 level >10.3 ng/ml indicates a high risk of chronic kidney disease stage 3-4 stage development (sensitivity 60%, specificity 75%) and can be considered as a risk factor for development of cardiorenal syndrome in HF patients.Conclusion. Galectin-3 level in patients with HF is more influenced by the degree of reduction in GFR rather than the left ventricular systolic function impairment.